PSXV-13 Rumen fermentation and rumen microorganism enzymes activity of Oura-type Tibetan sheep in different seasons. (7th December 2018) - Wang, C; Wu, J; Casper, D; Lang, X; Pan, F; Song, S; Wang, F; Gong, X
Abstract: Seasonal changes offer challenges for formulating feeding programs for Oura-type Tibetan sheep. The objective was to collect ruminal samples from ten ruminally cannulated 1.5-year-old Oura-type Tibetan wethers (average BW 58.67kg) to assess grazing pasture quality and ruminal parameters during the 4 grazing seasons. Ruminal samples were collected during the four grazing seasons at 0, 2, 4, 6, and 12 h after grazing to determine ruminal pH, NH3-N, microbial crude protein (MCP), volatile fatty acids (VFA), and microbial enzymes activity. Pasture samples collected at the same time as rumen samples were analyzed for nutrient concentrations of DM, CP, NDF, ADF, EE, Ash, Ca, and P. Data were analyzed as a 4 x 4 factorial of grazing season and sampling time using a completely randomized design. Summer pasture CP content (15.5%), ruminal NH3-N (7.42mg/100mL), and ruminal protease activity (0.348 U/mg protein) all reached peak (P＜0.05) compared to winter pasture CP content (3.68% DM), ruminal NH3-N (1.18 mg/mL), and protease activity(0.177U/mg protein) were relatively low. Protease activities increased after grazing up to 2 h and then decreased to the lowest at 6 h in all seasons except autumn. Ruminal lipase activities (0.055～0.070 U/mg protein) were low in all seasons but peaked in summer (0.070U/mg protein). Ruminal endoglucanase activity was high (P < 0.05) in spring and winter (0.105 U/mg protein and 0.106 U/mg protein) compared to summer and autumn (0.070 U/mg protein and 0.092 U/mg protein). On the contrary, ruminal total VFA, propionate, and butyrate (P ＜ 0.05) concentrations were higher (P < 0.05) in summer and autumn than that in spring and winter. Ruminal MCP and protease activity decreased (P < 0.05) after grazing in summer and autumn respectively. Season and grazing time had effects on Oura-type Tibetan sheep that nutritional supplementation is necessary for the sheep survival and improving performance. Key Words: